Glycome Profiling and Bioprospecting Potential of the Himalayan Buddhist Handmade Paper of Tawang Region of Arunachal Pradesh - Rather, Muzamil Ahmad; Dolley, Anutee; Hazarika, Nabajit; Ritse, Vimha; Sarma, Kuladip; Jamir, Latonglila; Satapathy, Siddhartha Shankar; Ray, Suvendra Kumar; Deka, Ramesh Chandra; Biswal, Ajaya Kumar; Doley, Robin; Mandal, Manabendra; et al. (Frontiers in Plant Science, 2022)
Paper and pulp industry (PPI) is one of the largest industries that contribute towards the growing economy of the world. While the wood remains the primary raw material of the PPIs, the demand for paper has also grown alongside the expanding global population leading to deforestation and ecological imbalance. Wood-based paper production is associated with enormous utilization of water resources, and release of different wastes and untreated sludge that degrades the quality of environment and makes it unsafe for living creatures. In line with this, the indigenous handmade paper making from the bark of Daphne papyracea, Wall. ex G. Don by the Monpa tribe of Arunachal Pradesh, India is considered as a potential alternative to non-wood fiber. This study discusses the species distribution modeling of D. papyracea, community-based production of the paper, and glycome profiling of the paper by plant cell wall glycan-directed monoclonal antibodies. The algorithms used for ecological and geographical modelling indicated the maximum predictive distribution of the plant towards the western parts of Arunachal Pradesh. It was also found that the suitable distribution of D. papyracea was largely affected by the precipitation and temperature variables. Plant cell walls are primarily made up of cellulose, hemicellulose, lignin, pectin, and glycoproteins. N¬on-cellulosic cell wall glycans contribute significantly to various physical properties such as density, crystallinity, and tensile strength of plant cell walls. Therefore, a detailed analysis of non-cellulosic cell wall glycan through glycome profiling and glycosyl residue composition analysis is important for the polymeric composition and commercial processing of D. papyracea paper. ELISA based glycome profiling result demonstrated that major classes of cell wall glycans such as xylan, arabinogalactans, and rhamnogalacturonan-I were present on D. papyracea paper. The presence of these polymers in the Himalayan Buddhist hand-made paper of Arunachal Pradesh is correlated with its high tensile strength. The results of this study imply that non-cellulosic cell wall glycans are required for the production of high-quality paper. To summarize, immediate action is required to strengthen the centuries-old practice of hand-made paper, which can be achieved through education, workshops, technical know-how, and effective marketing aid to entrepreneurs.